La formación docente en educación inclusiva de las licenciaturas de la Facultad de Educación de la Universidad de los Andes (2020)
The aim of this study was to understand how the Bachelor?s Degree Programs in Education at Universidad de Los Andes are training future teachers to support the learning process of the population with disabilities from an inclusive education approach. To that end, this study aligns with the Critical Paradigm, under a qualitative approach, and uses a Case Study. Following a document review, surveys, interviews and a focus group, a Thematic Analysis was carried out using five categories: human rights, inclusive education, teacher training, disability and diversity. The results show that there is no teacher training with an inclusive education approach to disability within the bachelor?s degrees of the Faculty of Education at Universidad de Los Andes.